Behind the mask : gender hybridity in a Zapotec community. - Mirandé, Alfredo (The University of Arizona Press, 2017)
"This book challenges Mexican narratives of the partriarchal gender binary by looking at the Muxes, a gender fluid indigenous group readily accepted by their community"--Provided by publisher.